'Go Out and Study the Land' (Judges 18:2): Archaeological, Historical and Textual Studies in Honor of Hanan Eshel - Maʾir, Aharon (Supplements to the Journal for the Study of Judaism, 2011)
The volume contains the 22 papers presented to Hanan Eshel before his death, covering topics in archaeology, history, and textual studies, with a particular emphasis on aspects relating to the Dead Sea Scrolls, spanning the late Iron Age through late Antiquity